Cyclic fluctuations, climatic changes and role of noise in planktonic foraminifera in the Mediterranean Sea - CARUSO, Antonio; VALENTI, Davide; FIASCONARO, Alessandro; SPAGNOLO, Bernardo; GARGANO M. E (Fluctuation and Noise Letters, 2005)
The study of Planktonic Foraminifera abundances permits to obtain climatic curves on the basis of percentage ratio between tropical and temperate/polar forms. Climatic changes were controlled by several phenomena as: (i) Milankovitch’s cycles, produced by variations of astronomical parameters such as precession, obliquity and eccentricity; (ii) continental geodynamic evolution and orogenic belt; (iii) variations of atmospheric and oceanic currents; (iv) volcanic eruptions; (v) meteor impacts. But while astronomical parameters have a quasi-regular periodicity, the other phenomena can be considered as “noise signal” in natural systems. The interplay between cyclical astronomical variations, the “noise signal” and the intrinsic nonlinearity of the ecologic system produces strong glacial or interglacial period according to the stochastic resonance phenomenon.